HIV-1 Rev Multimerization: Mechanism and Insights - Vercruysse, Thomas; Daelemans, Dirk (Current HIV Research, 2013)
To export intron-containing viral mRNAs that encode the structural components of new viral particles from the nucleus to the cytoplasm, HIV-1 uses the cellular CRM1 export pathway that is exploited by the viral Rev protein. Rev multimerizes on the Rev response element (RRE) present in the intron-containing RNA species to bridge these to the cellular export factor CRM1. As a result, this Rev-RRE complex is exported to the cytoplasm. This review provides a systematic overview of different aspects of the crucial function of Rev multimerization, such as co-operative Rev-Rev and Rev-RNA interactions, the biological function of Rev multimerization, the relevance of Rev multimerization in the absence of RRE and its potential as a therapeutic target.
Keywords: multimerization